Physician Assistant Students' Knowledge of Zika Virus: A Pilot Study. (April 2020) - Wishner, Carolina; Taylor, Colleen; Leigh, Laurasona; Williams, Monica; Bell, Mary Ann; Luebke, Suzanne
Objective: The aim of this study was to assess physician assistant students' knowledge about the screening, transmission, management, and prevention of Zika virus infection. Background: It is important for health care providers in the United States to recognize the symptoms of Zika so that they can screen, diagnose, and or treat persons exposed to or infected by the virus. Physician assistant students, on completion of their educational program and passing their board examinations, provide care for patients in primary care or specialty settings where they may treat patients who either have the virus or post-virus exposure. Methods: A convenience sample of 37 students enrolled in a physician assistant studies program in the Midwestern United States completed an in-person self-administered paper-and-pencil questionnaire that tested their knowledge about Zika virus infection. Results: All the respondents knew that the disease is of viral origin; however, only 89% knew that mosquitoes were the natural host. Primary modes of transmission were identified as sexual contact and blood transfusion (47% and 44% of respondents respectively); 47% incorrectly identified amniotic fluid as a transmission mode. More than half (61%) knew that health care providers should ask pregnant women about any possible virus exposure before and during pregnancy at each prenatal visit. Most respondents knew that muscle/joint pain (67%) was one of the symptoms of Zika infection, but only 39%, 25%, and 19% also identified low-grade fever, maculopapular rash, and conjunctivitis respectively as other symptoms. Some participants incorrectly identified antivirals (44%) and nonsteroidal anti-inflammatory medications (36%) rather than the recommended treatments of pain relief (30%) and fever relief (42%) medications for clinical management of the disease.